Światopoglądy młodopolskie w teatralnym lustrze XXI wieku. „Termopile polskie” Tadeusza Micińskiego i Jana Klaty - Brzozowska, Sabina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The previous attempts to present Tadeusz Miciński’s The Polish Thermopylae on the stage ended in either a complete failure or at least unfulfilled expectations. The multi-dimensional text-charade, full of numerous historical and philosophical references, constitutes a true challenge for an audience and a director. The ideological potential of the text encourages risky updates and simplifications. The plot of Miciński’s play is set in the years 1787–1813, starting with the meeting of King Stanisław August with Empress Catherine II and ending with the death of Prince Józef Poniatowski in the Elster River; yet, it takes place in the head of the dying prince. The Polish Thermopylae condenses time in a mysterious way and provokes the spectator to interpret historical events from the perspective of a mystery play. Jan Klata, the director, abandons allusions to a mystery play, uses many cliches from the sphere of pop-culture, and exposes the presence of the grotesque in Miciński’s play. In his impressive post-modern show, reality is arranged like a video clip: a juxtaposition of war and sports and erotic conquest, a conventional presentation of Empress Catherine II as the insatiable Messallina, a gymnastic amploi of Patiomkin as an allusion to Putin’s muscle flexing are not an intellectual challenge for the contemporary audience. And the ideal of Miciński’s theatre is the theatre being the judgement of conscience, the theatre being the mirror, the “mouse-trap” that never becomes out of date.